Diversity of plant species for food coloring in Vietnam - NGUYEN THI LUONG; NGUYEN VAN HOP; NGUYEN VAN QUY; VO MINH HOAN (Nusantara Bioscience, 2023)
Abstract. Luong NT, Hop NV, Quy NV, Hoan VM. 2023. Diversity of plant species for food coloring in Vietnam. Nusantara Bioscience 15: 95-104. Using natural colors of plants for food processing is an inevitable trend for the safety of consumers' health. It also provides essential vitamins, minerals, and nutrients to the body. This study aimed to systematize indigenous knowledge about food coloring plants of 11 ethnic groups in North, Central, and South Vietnam. Methods of ethnobotanical investigation, field investigation under the instruction of local people, and inheritance of documents combined with data analysis were employed. Therefore, 110 species of vascular plants belonging to 54 families of food coloring were discovered in Vietnam. As a result, 28 species were used with high frequency, and 15 species were identified as conservation values domestically and globally. Besides, the richness of folk knowledge of local people was also recorded. Five plant life forms were identified, i.e., shrubs, wood, vines, herbaceous, and bamboo. Eleven plant parts were used; leaves accounted for the largest proportion (36.36%), followed by fruit, wood, flowers, bark, seeds, tubers, rhizomes, young tops, sap, and roots. Ten different colors were created from plants for food dyeing; red accounted for the highest percentage (28.18%), followed by yellow, green, black, and gray was the lowest (0.91%). Most plants can produce monochromatic colors (94/110 species). Of the species recorded, 39.09% were wild plant species, 40.00% were cultivated, and 20.91% of species could be found in the wild or cultivated. The number of species that gave color to cook rice was dominant (68.18%), followed by cakes, drinks, and soups, soaked in alcohol and sticky. This study shows the diversity of species composition, the abundance of traditional knowledge, and the potential of plants for food coloring in Vietnam. In the future, in-depth studies on the species’ nutritional composition, chemistry, vitamins, and extracts should be proposed, contributing to the food and beverage industry and especially maintaining and developing a culinary culture imbued with national identity.